2004
DOI: 10.1063/1.1702143
|View full text |Cite
|
Sign up to set email alerts
|

Very high-efficiency and low voltage phosphorescent organic light-emitting diodes based on a p-i-n junction

Abstract: Green phosphorescent organic light-emitting devices (OLEDs) employing tris(2-phenylpyridine) iridium doped into a wide energy gap hole transport host have been studied. N,N,N′,N′-tetrakis(4-methoxyphenyl)-benzidine doped with 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane is used as a hole injection and transport layer, 4,7-diphenyl-1,10-phenanthroline and cesium are coevaporated as a n-doped electron transport layer, and an intrinsic emission layer is sandwiched between these two doped layer. Such a p-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
110
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(115 citation statements)
references
References 22 publications
4
110
0
1
Order By: Relevance
“…This approach enables internal quantum efficiencies reaching unity [1] and operational lifetimes suitable for commercial display applications. [2,3,4,5,6] A common technique to fabricate multicolor pixelated OLED devices is shadow mask patterning. However, there are severe limitations…”
mentioning
confidence: 99%
“…This approach enables internal quantum efficiencies reaching unity [1] and operational lifetimes suitable for commercial display applications. [2,3,4,5,6] A common technique to fabricate multicolor pixelated OLED devices is shadow mask patterning. However, there are severe limitations…”
mentioning
confidence: 99%
“…High-efficiency OLEDs have also been reported in various HIL/HTL configurations. [4][5][6][7][8] Furthermore, low-voltage and high-efficiency OLEDs can be realized with a p-doped HIL [9][10][11] in which the layer thickness can be readily adjusted for optimal light extraction. It has been suggested that the enhanced performance in HIL/HTL devices is due to a sequence of cascaded hole-injection barriers present in the HIL/HTL/ETL structure, which produces a "balanced" electron-hole recombination at the HTL/ETL interface.…”
mentioning
confidence: 99%
“…The grounds for achieving very similar electrical properties of the OLED samples is to use doped ETL and HTL layers and a p-i-n OLED structure. 15,16 Having this in mind, one can determine g cb as a constant fitting parameter by comparing measured EQE values (without a half-ball lens) and simulated EQE air values using Eq. (16).…”
Section: Verification Of the Model And Discussionmentioning
confidence: 99%
“…15,16 Having this in mind, one can determine g cb as a constant fitting parameter by comparing measured EQE values (without a half-ball lens) and simulated EQE air values using Eq. (16). The values for the measured EQE are taken at a low current density before the efficiency roll-off sets in (Fig.…”
Section: Verification Of the Model And Discussionmentioning
confidence: 99%
See 1 more Smart Citation